SOME FEATURES OF GEOID’S RELIEF REFINEMENT FROM SATELLITE GRAVIMETRIC DATA - DUBOVENKO, Yu. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
The modern stage of the geoids form (undulations) revision is analyzed taking into account parameters of the Earth gravity model EGW96 for WGS-84 ellipsoid. Relations of the gravity with the geoid’s undulations are illustrated by means of example of the geoid’s sagging accounted after the earthquake on Sumatra as far as of example of revision of the parameters of density anomalies point sources in northern Atlantic by the known geoid’s anomalies. Necessity to account the indirect effects is pointed. To assign the influence of the time variations of gravity due to planet movement dynamics in its orbit relativistic the expressions of the mass and bodies full energy increasing in gravity field are formulated. In areas of highly gradient gravity the quantity of the full energy fluctuations is comparable with observation errors of ^g . Use of the formulas in practical computing is obstructed because of difference of the existing reference systems.